The influence of FoMO and Social Media Marketing on purchasing decisions for Mixue Ice Cream & tea products - Fitriani, Anisa; Viyani, Ari Okta (Portofolio: Jurnal Ekonomi, Bisnis, Manajemen, dan Akuntansi, 2024)
Mixue Ice Cream & Tea is an ice cream and cold drink franchise company originating from China founded in 1997. Mixue is popular because it goes viral in cyberspace so that the massive opening of Mixue outlets in Indonesia does not escape the viral phenomenon. The research objective is to determine: the influence of FoMO and Social Media Marketing on purchasing decisions for Mixue Ice Cream & Tea products. The data source used is primary and researchers conducted research by distributing questionnaires to 209 respondents of Mixue Ice Cream & Tea customers in Indonesia with the criteria of having bought Mixue products 2 times. This type of research uses quantitative methods. The results showed that FoMO and Social Media Marketing had a positive and significant influence on purchasing decisions.